Analyzing media representations of mental illness: Lessons learnt from a national project. (June 2013) - Whitley, Rob; Berry, Sarah
<x xml:space="preserve">Abstract</x> Background: Much research suggests that the general public relies on the popular media as its main source of information about mental illness. Assessing media representations of people with mental illness is vitally important, given that research suggests that the media exerts a strong, often negative, influence on public attitudes. Aims: Few specific methodological guidelines exist to help researchers conducting media analyses. The aim of this article is to describe lessons learnt from over 2 years of experience conducting a large-scale systematic national project analyzing media portrayals of mental illness. Methods: We do this by presenting and discussing five of the biggest challenges (and associated solutions) that have faced us as we have progressed in our national study. Results: These are as follows: (i) defining relevant search terms; (ii) developing appropriate inclusion and exclusion criteria; (iii) creating a coding scheme; (iv) choosing strategies of analysis and dissemination and (v) staffing and training issues. Conclusion: It is our hope that the information purveyed in this article may help those analyzing media representations of mental illness elsewhere.